Family Business: Affect and Reconciliation in A Brimful of Asha - Filewod, Alan (Studies in Canadian Literature, 2015)
This analysis of Ravi Jain’s and Asha Jain’s A Brimful of Asha (2012) examines the text of the play as an instance of performance that functions as a staged autopsy of family crisis and reconciliation. In A Brimful of Asha, mother and son perform a shared, if conflicted, memoir about an immigrant family’s negotiation with cultural tradition (in this case, over the parental responsibility to arrange a marriage for a son who refuses to comply). Considered in terms of theatrical life writing, mother and son share the stage to demonstrate, through comic monologues and fond bickering, that the life of the individual is the life of the family. That the two cannot be separated is the lesson that emerges from the incident that the play relates and the production reconciles. The negotiation of subject and performativity produces the imbalanced affect of the show, in which Asha’s low-affect performativity counters (and indeed controls) Ravi’s high-affect performance. A Brimful of Asha is on the narrative level a story about a family crisis over arranged marriage, but the conflict that Asha’s presence on stage reconciles is a deeper family crisis about theatre. This deep narrative is a restaging of the play’s origins, because the performance is both the result of and the solution to the family crisis. Their reconciliation enacts the entrepreneurial skill that has made the family successful in business by transforming a family crisis into a theatrical hit, and demonstrates the initiative, adaptivity, and resourcefulness of an immigrant family willing to try something radical and new to make a better life.